Analisis Faktor-Faktor yang Memengaruhi Transformasi Pendidikan Islam di Era Digital - Lailatul Isti’anah; Syamsul Aripin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of digital technology has brought significant changes to various aspects of education, including Islamic education. The transformation of Islamic education in the digital era is crucial to ensure that learning methods remain relevant, interactive, and able to accommodate the needs of students who are increasingly accustomed to technology. This study aims to analyze the factors influencing the transformation of Islamic education through a literature study approach. The research method was carried out by collecting and reviewing various scientific journals, educational reports, and articles related to digital-based Islamic learning innovations, then analyzing them descriptively to identify key factors. The analysis results indicate several factors that play a significant role in the transformation of Islamic education, namely technological advances, the use of digital media, institutional dynamics, changes in teacher roles, the readiness of educators, the integration of Islamic values, and infrastructure and access to technology. Each factor contributes to the effectiveness of digital learning implementation, but adaptive and contextual implementation is key to success. The transformation of Islamic education in the digital era requires the implementation of a comprehensive strategy, considering teacher readiness, curriculum quality, technological support, and active student involvement to maintain Islamic values. These findings can serve as a reference for Islamic educational institutions in designing adaptive and innovative learning policies and practices in the digital era.